IMPACT OF THE MATERNAL REFLECTIVE METHOD ON SPEECH AND SOCIAL SKILL DEVELOPMENT IN DEAF CHILDREN AT SCHOOL FOR CHILDREN WITH SPECIAL NEEDS (SLB) B KARYA MURNI MEDAN - Epi Samosir; Risydah Fadilah; Amanah Surbakti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This research aimed to examine the influence of the Maternal Reflective Method (MRM) on improving the speech and social interaction skills of deaf children at SLB-B Karya Murni Medan. The low verbal communication and social interaction abilities among deaf children present a crucial problem, impacting their learning development and social adaptation. Using a quantitative approach with a quasi-experimental pretest-posttest control group design, this study involved elementary-level deaf students, divided into experimental and control groups. Data were collected through structured observation using instruments that had undergone validity and reliability testing. Data analysis using t-tests showed that the experimental group experienced a significant increase in average scores from 23 to 71 in both speech and social skills compared to the control group. The improvement in speech skills was evidenced by the children's enhanced ability to express ideas/concepts with clearer vocalization, more appropriate intonation, more accurate pronunciation, and improved word order and speech fluency. Furthermore, the implementation of MRM significantly affected the deaf children's social skills, demonstrated by an increased frequency of interaction initiation, more active responses to conversational partners, and the manifestation of more adaptive social attitudes in small group activities. While showing positive results, this study was limited to a single institution with a restricted number of subjects, thus requiring cautious generalization. The effectiveness of MRM is highly dependent on facilitator quality and individual child characteristics. Future research can explore these factors more deeply and address challenges in MRM implementation, such as children's resistance to the reflective process. This research recommends integrating MRM as one of the supporting methods in SLB learning programs, with consideration for adaptation to each school's specific context and resources.